Diet and trophic groups of an aquatic insect community in a tropical stream - Motta, R. L. [UNESP]; Uieda, Virginia Sanches [UNESP] (Instituto Internacional de Ecologia, 2004)
A dieta e o grupo trófico de uma assembléia de insetos aquáticos foi estudada em um riacho tropical. Os gêneros de algumas ordens de insetos, como Lepidoptera, Ephemeroptera, Plecoptera, Odonata e Hemiptera, apresentaram especialização alimentar. Por outro lado, as ordens Trichoptera, Coleoptera e Diptera mostraram grande variação na dieta, com gêneros de diferentes grupos tróficos. Alguns gêneros das ordens Trichoptera, Lepidoptera, Coleoptera e Diptera apresentaram variação sazonal na dieta relacionada a mudanças na composição da comunidade e à dieta generalista desses gêneros. Entretanto, a comparação sazonal de grupos tróficos mostrou diferenças não significativas estatisticamente. A grande importância da matéria orgânica, um recurso não limitado, na dieta dos insetos aquáticos no Ribeirão do Atalho pode ser a explicação para a estabilidade da organização trófica dessa comunidade.

The diet and trophic groups of an assemblage of aquatic insects were studied in a tropical stream. Genera of the orders Ephemeroptera, Odonata, Plecoptera, Lepidoptera, and Hemiptera showed feeding specialization. Others, such as Trichoptera, Coleoptera, and Diptera, showed great diet variation with genera of different trophic groups. Seasonal variation of insect diet, evident only for some genera of the orders Trichoptera, Lepidoptera, Coleoptera, and Diptera, was due to the differences observed in community composition and to generalist habits of these genera. However, the seasonal comparison of trophic groups showed no significant statistical differences. The great importance of organic matter, a non-limited resource, in the diet of Ribeirão do Atalho aquatic insects may be the explanation for the trophic stability in this community organization.
Dieta e grupos tróficos de uma comunidade de insetos aquáticos em um riacho tropical
Keywords: insetos aquáticos; dieta; grupos tróficos; riacho tropical; aquatic insects; diet; trophic groups; tropical stream